Whole-Exome Sequencing in a Cohort of High Myopia Patients in Northwest China - Liu, Yang; Zhang, Jin-Jin; Piao, Shun-Yu; Shen, Ren-Juan; Ma, Ya; Xue, Zhong-Qi; Zhang, Wen; Liu, Juan; Jin, Zi-Bing; Zhuang, Wen-Juan (Frontiers in Cell and Developmental Biology, 2021)
High myopia (HM) is one of the leading causes of visual impairment worldwide. In order to expand the myopia gene spectrum in Chinese population, we investigated genetic mutations in a cohort of 27 families with high myopia from northwest China by using whole-exome sequencing (WES). Genetic variations were filtered using bioinformatics tools and cosegregation analysis. A total of 201 candidate mutations were detected, and 139 ones were cosegregated with the disease in the families. Multistep analysis revealed four missense variants in four unrelated families, including c.904C>T (p.R302C) in CSMD1, c.860G>A (p.R287H) in PARP8, c.G848A (p.G283D) in ADAMTSL1, and c.686A>G (p.H229R) in FNDC3B. These mutations were rare or absent in the Exome Aggregation Consortium (ExAC), 1000 Genomes and genomAD databases, indicating they are new candidate disease-causing genes. Our findings not only expand the myopia gene spectrum, but also provide reference information for further genetic study of heritable high myopia.